SUBJECTIVE WELL-BEING OF NEET BASED ON GENDER AND GENERATION SURVEY IN MOLDOVA - Maxim Slav (Economy and Sociology)
EET is an umbrella term for those who struggle with their school-to-work transition. It is a consensus today that NEET is an acutely heterogeneous group, and there are varying ways to classify its members. Some of them deliberately reject or postpone the school-to-work transition, for example, because they choose to fulfill their traditional gender role. In these cases, NEET is a conscious choice. In this article, the NEET classification was based on the individuals' well-being. Moldova gives a good opportunity to study NEET as this Eastern European country suffers from simultaneous socio-economic crises, including high emigration and poverty rates. The data were taken from the Gender and Generation Survey (GGS) conducted in 2020. Based on the previous research, the 15 - 29 age group was chosen (326 observations comply with the NEET conditions and are complete). The author chose the questions related to the following aspects of well-being: happiness, life satisfaction, and depression sentiments. The variables are categorical, and they were analyzed with a Latent Class Model. There are substantial correspondences between the NEET well-being classes and the causes of NEET. The results supplement the current knowledge on NEET heterogeneity from the side of self-assigned well-being rather than socio-economic inequalities.